Effect of wafer resistivity and light intensity on the topography of porous silicon surfaces produced by photo chemical method - Amjad Hussen Jassem; Hanaa E. Jassem; Shihab Ahmaed Kalaf; Najat A. Dahham (Tikrit Journal of Pure Science, 2023)
This study includes the effect of wafer resistivity and intensity  of light on topography of porous silicon surfaces which produced by photo chemical etching method, the results showed that changing of the resistivity led to change the  porosity, where it found the porous silicon layer be less of high value resistivity.